Pengembangan Sistem Informasi Marketing Automation Menggunakan RFM Dan Topsis Pada Lotus Asia Tours - I Putu A Angga Krishna; Retno Indah Rokhmawati; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Customer Relationship Management (CRM) is a strategy in business which coordinates the process internal organization with customer to gain some profit for the company. This research was done in Lotus Asia Tours as one of the companies which one of its activities was sending some promotion to customers. Actually, Lotus Asia Tours had its own different kinds of customer, they are; ordinary customers and big type of customers. The application of CRM Operational method by applying Marketing Automation and Customer Segmentation which had function in sending some promotion to customers based on types of customer themselves which were gotten from the result of segmenting the customers based on data transaction.In segmenting the customers, the researcher used Recency, frequency, Monetary method where the customer's data transaction would be grouped based on the RFM variable by using K-Mean and in order to stipulate the group ratings, the researcher used TOPSIS.The result of the group ratings would be divided into four types of customers, they are; Platinum, Gold, Silver and Bronze. The result of applying this system uses utility system was 66% valid which meant that Lotus Asia Tours was satisfied because of the existence of that information system of marketing automation